Gestión financiera y la rentabilidad para la Comercializadora COILE S.A. Agencia Loja, periodo 2018-2022 - Carrión Vásquez, Mayra Alejandra (2024)
This research work aims to obtain a comprehensive understanding of the financial management and profitability of the COILE SA Trading Company, Loja Agency. The general objective was to determine the impact of financial management on the profitability of COILE S.A. Trading Company, Loja Agency, during the period 2018-2022. It has been demonstrated to have a significant relationship on the company's profitability, as revealed by the detailed analysis of financial relationships. This study employed a non-experimental and descriptive approach, combining qualitative and quantitative elements. A mixed approach was adopted, integrating inductive and analytical methods, as well as synthetic and mathematical methods, along with various techniques such as financial analysis, content analysis, and financial modeling. Data collection included the review of financial statements, interviews, and content analysis. Among the results obtained, the financial report highlights improvements in profitability despite liquidity and indebtedness challenges. The Pearson correlation method highlights the interconnection between financial and strategic decisions, emphasizing the importance of effective financial management in driving profitability over time. The application of the Dupont method reveals a positive trend in relation to sales and profit, concluding with the proposal of a comprehensive plan to enhance profitability and stabilize the financial structure. In conclusion, the analysis of relationships between various financial variables provides valuable insight into their interaction and dependence. It is emphasized that effective liquidity management and debt restructuring are essential to overcome the identified challenges. Recommendations focus on improving liquidity, optimizing operational efficiency, and ensuring the sustainability of improvements, proposing a gradual implementation and continuous staff training to promote the growth and sustainability of COILE S.A. Loja Agency.